Cooperative Adaptive Cruise Control of Vehicle Platoons with Fading Signals and Heterogeneous Communication Delays. Issue 2 (2020) - Song, Xiulan; Xiao, Feng; Peng, Hong; He, Defeng
Abstract: This paper proposes a new cooperative adaptive cruise control (CACC) approach of vehicle platoons with fading signals and heterogeneous communication delays. The CACC model with variable input delays is established to describe the varying time-delays from transmitting acceleration of the front vehicle. The fading signal gains may be unknown and uncertain due to heterogeneous V2V wireless channels. Then a set of decentralized time-delay feedback CACC controllers is computed in such way that each vehicle evaluates its own control strategy using only neighborhood information. In order to establish string stability of the platoon with the decentralized controllers, some sufficient conditions are obtained in form of linear matrix inequalities. The scenarios, consisting of seven different cars with heterogeneous wireless channels, are used to demonstrate the effectiveness of the presented method.